(untitled) (Jurnal Teknologi (Sciences & Engineering), 2016)
Enhanced absorption and emission cross-sections of rare earth doped binary glasses are highly demanding for various photonic applications. Determining the right glass compositions with appropriate rare earth dopants remain challenging. Different microscopic mechanisms responsible for optical enhancement and quenching are not fully understood. In this view, we prepare a series of glasses with composition (80-x)TeO2-20ZnO-(x)Sm2O3, where 0 ≤ x ≤ 1.5 mol% using melt quenching technique. X-ray diffraction (XRD), Photoluminescence (PL) and Ultraviolet Visible Near-Infrared (UV-Vis-NIR) spectroscopic measurements are carried out to inspect the samarium concentration dependent absorption and emission features of the prepared glasses. Physical properties such as glass density and molar volume are found to be in the range 5.57-5.61 g cm-3 and 25.84-26.15 cm3 mol-1, respectively. XRD pattern verifies the amorphous nature of the prepared samples. The UV-Vis-NIR absorption spectra reveal nine peaks centered at 470, 548, 947, 1085, 1238, 1385, 1492, 1550 and 1589 nm. These bands arise due to 6H5/2→4I11/2, 4G5/2, 6F11/2, 6F9/2, 6F7/2, 6F5/2, 6F3/2, 6H15/2, and 6F1/2 transitions, respectively. PL spectra under the excitation of 452 nm display four emission bands centered at 563, 600, 644 and 705 nm corresponding to 4G5/2→6H5/2, 6H7/2, 6H9/2 and 6H11/2 transitions of samarium ions. The mechanism of photoluminescence enhancement is identified, analyzed, and understood. A correlation between samarium concentration and optical response is established. This composition may be useful for fabricating various optical devices